2015
DOI: 10.3892/mmr.2015.4000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the coagulation factor V gene and risk of femoral head osteonecrosis

Abstract: Osteonecrosis of the femoral head (ONFH) is characterized by the death of the cellular portion of the femoral head due a reduction or disruption in the blood supply. Certain studies have implicated coagulation disorders, including thrombophilia and hypofibrinolysis, in the pathogenesis of ONFH. The factor V (F5) Leiden mutation has been suggested to be a genetic risk factor for venous thromboembolism and osteonecrosis in Caucasian individuals, however, this association remains controversial in other population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Hematologic evidence of intraosseous hypercoagulability has been found on the basis of both human and animal studies of ON [ 24 , 25 ]. Hypercoagulability, a pathological process mediated by a variety of factors and hematological changes, plays an important role in the process of thrombus formation [ 26 ]. Moreover, steroid treatment enhances hypercoagulability, induces venous thrombosis, decreases blood circulation, and leads to ONFH [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hematologic evidence of intraosseous hypercoagulability has been found on the basis of both human and animal studies of ON [ 24 , 25 ]. Hypercoagulability, a pathological process mediated by a variety of factors and hematological changes, plays an important role in the process of thrombus formation [ 26 ]. Moreover, steroid treatment enhances hypercoagulability, induces venous thrombosis, decreases blood circulation, and leads to ONFH [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although ONFH is a common complication deteriorating the treatment of SLE, details of the pathogenesis are not well established. Because venous thrombosis and resultant blood flow obstruction mediated by thrombophilia or hypofibrinolysis are generally assumed to develop ONFH [ 18 , 19 ], most of gene studies have focused on gene polymorphisms affecting the coagulation and fibrinolytic systems [ 8 , 9 ]. Recent studies, however, reported that immunologic factors might develop ONFH [ 6 , 7 ] and few genetic studies were performed to reveal their roles in the development of SLE_ONFH [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…All reactions were performed following the manufacturer's protocol. Details regarding the PCR reaction and TaqMan assay have been described previously [ 9 ]. The fluorescence data files from each plate were collected and analyzed using automated allele-calling software (SDS 2.2, Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify the genetic factor of IONFH, many candidate gene analyses have been performed 14 ; however, these studies have only examined specific SNPs in candidate genes related to plausible pathogenesis of ONFH, such as coagulation 15 , fibrinolysis 16 , angiogenesis 17 , hypoxic response 18 , and steroid 19 and alcohol metabolisms 20 . No definite susceptibility genes have been identified yet.…”
Section: Introductionmentioning
confidence: 99%